Idris Bidlisis Prefatory Poem to Hast Bihist VI: Editio Princeps and Translation - Mustafa Dehqan (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2024)
A historian of Kurdish origin, Idris Bidlisi (1457-1520), is undoubtedly one of the most important intellectuals in the Ottoman-Iranian borderland in the late-fifteenth and early-sixteenth centuries. Although his Persian and Arabic works have been the focus of long-standing historical debates, there are as yet few proper, in-depth textual and critical editions. This is particularly true regarding Bidlisis Persian history of the first eight Ottoman sultans called Hast Bihist (The Eight Paradises) and especially its unpublished Book VI. This paper provides an editio princeps of Bidlisis Arabic prefatory poem to Book VI and its English translation.